Data Visualization Preferences in Remote Measurement Technology for Individuals Living With Depression, Epilepsy, and Multiple Sclerosis: Qualitative Study - Simblett, Sara; Dawe-Lane, Erin; Gilpin, Gina; Morris, Daniel; White, Katie; Erturk, Sinan; Devonshire, Julie; Lees, Simon; Zormpas, Spyridon; Polhemus, Ashley; Temesi, Gergely; Cummins, Nicholas; et al. (Journal of medical Internet research, 2024)
BACKGROUND: Remote measurement technology (RMT) involves the use of wearable devices and smartphone apps to measure health outcomes in everyday life. RMT with feedback in the form of data visual representations can facilitate self-management of chronic health conditions, promote health care engagement, and present opportunities for intervention. Studies to date focus broadly on multiple dimensions of service users' design preferences and RMT user experiences (eg, health variables of perceived importance and perceived quality of medical advice provided) as opposed to data visualization preferences. OBJECTIVE: This study aims to explore data visualization preferences and priorities in RMT, with individuals living with depression, those with epilepsy, and those with multiple sclerosis (MS). METHODS: A triangulated qualitative study comparing and thematically synthesizing focus group discussions with user reviews of existing self-management apps and a systematic review of RMT data visualization preferences. A total of 45 people participated in 6 focus groups across the 3 health conditions (depression, n=17; epilepsy, n=11; and MS, n=17). RESULTS: Thematic analysis validated a major theme around design preferences and recommendations and identified a further four minor themes: (1) data reporting, (2) impact of visualization, (3) moderators of visualization preferences, and (4) system-related factors and features. CONCLUSIONS: When used effectively, data visualizations are valuable, engaging components of RMT. Easy to use and intuitive data visualization design was lauded by individuals with neurological and psychiatric conditions. Apps design needs to consider the unique requirements of service users. Overall, this study offers RMT developers a comprehensive outline of the data visualization preferences of individuals living with depression, epilepsy, and MS.
Keywords: multiple sclerosis; dospělí; smartphone apps; qualitative; Epilepsy; Qualitative Research; Telemedicine; Female; data; Mobile Applications; application; Patient Preference; Adult; ženské pohlaví; lidé; Multiple Sclerosis; Wearable Electronic Devices; devices; wearables; Data Visualization; telemedicína; roztroušená skleróza; Focus Groups; depression; epilepsy; technology; epilepsie; Male; mHealth; Aged; mobilní aplikace; vizualizace dat; data visualization; zjišťování skupinových postojů; nositelná elektronika; pacientova volba; lidé středního věku; deprese; senioři; mužské pohlaví; Depression; feedback; Middle Aged; mobile phone; kvalitativní výzkum; users; Humans